AFDC Participation across Generations - Gottschalk, Peter (American Economic Review, 1990)
William Julius Wilson's influential book The Truly Disadvantaged (1987) has sparked a vigorous debate about the existence and causes of an urban underclass. While there is still no clear agreement about definitions, the growing literature on the underclass focuses both on traits of the current generation and the traits of their parents. If an underclass exists, its current members are assumed to live in deteriorating inner cities, to experience long spells of joblessness or welfare dependency, and/or to engage in illegal and antisocial activities. Furthermore, these traits are assumed to be correlated across generations, leading to a cycle of deprivation. In this paper, I focus on one such link across generations by examining the correlation in welfare participation of daughters and their parents. I first present the state of knowledge about the extent to which children of parents who received Aid to Families with Dependent Children (AFDC) are themselves more likely to participate in this welfare program. Second, I discuss the remaining gaps in our understanding and give several contrasting altemative explanations for the observed correlation, each with a different policy implication.